Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011. Issue 2 (17th January 2021) - Luo, Xiao-Wei; Chen, Chun-Mei; Li, Kun-Long; Lin, Xiu-Ping; Gao, Cheng-Hai; Zhou, Xue-Feng; Liu, Yong-Hong
Abstract: One new sesquiterpenoid, 1-methoxypestabacillin B (1 ), along with one known sesquiterpenoid (2 ) and six known chrodrimanin-type meroterpenoids (3 ‒8 ) were obtained from the solid cultures of a mangrove endophytic fungus Diaporthe sp. SCSIO 41011. Their structures including the absolute configuration at C-6 of compound 1, were determined by extensive spectroscopic analyses and ECD calculations. Meanwhile, the X-ray crystal structures and absolute configurations of two previously reported chrodrimanins E (3 ) and H (6 ), are described for the first time. All the compounds were examined for HIV latency-reversal and anti-influenza A virus activities. Graphical Abstract: